Ensuring the preservation of cultural values of the Garrison Church and the Church of Paraskeva in Lviv during the war - Волощенко, Станіслав; Шпак, Арсен (Київський національний університет імені Тараса Шевченка, 2022)
The proposed article is devoted to the issue of preservation from possible damage to the national heritage of the Garrison Church of the Holy Apostles Peter and Paul (Jesuit Church or Society of Jesus), as well as the Church of St. Paraskeva Friday in Lviv during the Russian-Ukrainian war (2014 – present). Circumstances of the full-scale military invasion of the Russian Federation into Ukraine on February 24, 2022, necessitated the immediate need to protect the country's cultural heritage. The urgency of the security component of the preservation of art objects was dictated by missile attacks in almost all regions of Ukraine, including the Lviv region. The security measures in which the authors of the article took part were conditioned by the possibility of rocket attacks on sacred monuments of Lviv and the possibility of their damage by fire or mechanical damage. These cultural values include altars, wooden sculptures, decorative elements, organs, and objects on the canvas of the Garrison Church, as well as a six-row wooden iconostasis of the Church of St. Paraskeva. The specifics of the material of art objects, their size, location, and in part restoration work, made it difficult to evacuate and preserve them in new circumstances. The authors characterize the newly acquired experience of securing the heritage of the 17th – 20th centuries. refractory materials in the outlined Lviv religious buildings. The article deals with artefacts that have been protected from the effects of missile damage. The stages of monument protection work are covered, which first of all consist of selecting and classifying refractory and heat-resistant materials, team involvement, photo-fixing, marking, inventory of objects, and direct security of art objects. The authors express their recommendations for practical solutions in uncertain conditions. For the first time since the restoration of Ukraine’s independence, such a practice has been used in architectural monuments of national importance in Ukraine.

Пропонована стаття присвячена проблематиці збереженості від можливих пошкоджень національного надбання Гарнізонного храму святих апостолів Петра і Павла (костел єзуїтів або Товариства Ісусового), а також церкви преподобної Параскеви П’ятниці у Львові під час російсько-української війни (2014 – до нині). Обставини повномасштабного військового вторгнення Російської Федерації до України 24 лютого 2022 р. зумовили негайну потребу в охороні культурної спадщини країни. Невідкладність безпекового компоненту збереження мистецьких об’єктів була продиктованою ракетними атаками майже усіх областей України, в тому числі Львівської області. Охоронні заходи, у яких брали участь автори статті, були зумовлені вірогідністю ракетних обстрілів сакральних пам’яток Львова та можливістю їхнього пошкодження наслідками пожежі чи ушкоджень механічного характеру. До цих культурних цінностей належать вівтарі, дерев’яні скульптури, елементи декору, орган й об’єкти на полотні Гарнізонного храму, а також шестирядний дерев’яний іконостас П’ятницької церкви. Специфіка матеріалу мистецьких об’єктів, їх розмір, розташування, почасти реставраційні роботи, ускладнювали проведення їх евакуації та збереження в нових обставинах. Автори характеризують новонабутий досвід узабезпечення спадщини XVII–ХХ ст. вогнетривкими матеріалами в окреслених львівських культових спорудах. У статті йдеться про артефакти, які вдалося оберегти від наслідків ракетних уражень. Висвітлюються етапи пам’ятко-охоронної праці, які найперше полягали у підборі та класифікуванні вогнетривких і термотривких матеріалів, залученні команди, фотофіксації, маркуванні, інвентаризації об’єктів, безпосередньому забезпеченню безпеки мистецьких предметів. Автори висловлюють власні рекомендації практичних рішень в невизначених умовах, позаяк вперше, з часу відновлення Незалежності України, подібна практика була застосована в пам’ятках архітектури національного значення України.
Забезпечення збереженості культурних цінностей Гарнізонного храму та церкви Параскеви у Львові в умовах війни
Keywords: cultural values; preservation of national heritage; the Russian-Ukrainian war; the Garrison Church; the Church of St. Paraskeva; Lviv; культурні цінності; збереження національної спадщини; російсько-українська війна; Гарнізонний храм; церква св. Параскеви; Львів